2018
DOI: 10.1021/acschemneuro.8b00200
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptors in Alcohol Use Disorder: Physiology, Plasticity, and Promising Pharmacotherapies

Abstract: Developing efficacious treatments for alcohol use disorder (AUD) has proven difficult. The insidious nature of the disease necessitates a deep understanding of its underlying biology as well as innovative approaches to ameliorate ethanol-related pathophysiology. Excessive ethanol seeking and relapse are generated by long-term changes to membrane properties, synaptic physiology, and plasticity throughout the limbic system and associated brain structures. Each of these factors can be modulated by metabotropic gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 201 publications
(401 reference statements)
3
23
0
Order By: Relevance
“…Specifically, the PAM potentiates Ca 2+ mobilization and hippocampal LTD without directly enhancing N-methyl-D-aspartate (NMDA) receptor function. Therefore, although mGlu 5 has been intimately linked with NMDA receptor-dependent plasticity (Joffe et al, 2018), the molecular pharmacology suggests those signaling pathways are likely not involved in the effects observed here. In addition, Balu et al (Balu et al, 2016) reported that VU0409551 treatment enhances PL-PFC Akt phosphorylation in a genetic model of schizophrenia-like deficits as well as in control mice.…”
Section: Discussionmentioning
confidence: 87%
“…Specifically, the PAM potentiates Ca 2+ mobilization and hippocampal LTD without directly enhancing N-methyl-D-aspartate (NMDA) receptor function. Therefore, although mGlu 5 has been intimately linked with NMDA receptor-dependent plasticity (Joffe et al, 2018), the molecular pharmacology suggests those signaling pathways are likely not involved in the effects observed here. In addition, Balu et al (Balu et al, 2016) reported that VU0409551 treatment enhances PL-PFC Akt phosphorylation in a genetic model of schizophrenia-like deficits as well as in control mice.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous studies have suggested that neuroimmune activation may play an important role in the development of addiction (for review, see (Coleman and Crews 2018)). Further, the identified interaction with mGlu2/3 is significant given the growing interest in mGluR2/3 as a therapeutic target of AUDs (Joffe et al 2018). Furthermore, ethanol induces many of the same effects in the brain that a viral pathogen would (i.e., increases in TLRs and other markers of inflammation; (Crews et al 2013; Crews and Vetreno 2014; 2016; Frank et al 2015; Hutchinson et al 2010; Knapp and Crews 1999; McCarthy et al 2017; Northcutt et al 2015)).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, there is interest in understanding the potential contribution of Group II metabotropic glutamate receptors (mGluRs), along with excitatory amino acid transporter 2 (EAAT2) also known as solute carrier family 1 member 2(SLC1A2) and glutamate transporter 1 (GLT1), for their role in AUDs (Joffe et al 2018). These Gi-coupled receptors are located both pre- (mGluR2 and mGluR3) and post- (mGluR3) synaptically and modulate glutamate release, in part by preventing excitotoxicity (Cartmell and Schoepp 2000; Conn and Pin 1997; Forsythe and Barnes-Davies 1997; Scanziani et al 1997; Schoepp 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study has provided evidence for mGlu 5 in sleep/wake architecture, suggesting that mGlu 5 allosteric modulators may have potential to remedy certain sleep disorders [66]. Certainly, investigation of mGlu allosteric modulators for substance use disorders [67], epilepsy [68], major depressive disorder [69], and Alzheimer's disease [70] are contexts in which there is exciting work being accomplished within the field of allosteric modulators and mGlu receptors. As the drug discovery process is a circular method, continued research efforts will likely lead to even more insights into the neuropharmacology surrounding mGlu allosteric modulators and their usefulness as therapeutics in CNS disorders.…”
Section: Discussionmentioning
confidence: 99%